Clinical, etiological, biochemical, microbiological and neurosonogram factors in related with neonatal seizures in Visakhapatnam, India - Rao, Marpi Suryaprasada; Rao, Gavara Chinna; Sultana, Ayesha; Karthik, Putrevu Jagannadha (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal seizure is a common neurological problem in the neonatal period. Detection of seizure, its etiology, and clinical types is important for guiding therapy. A varied number of conditions are capable of causing seizures in the neonatal period. The aim was to study biochemical, microbiological and, nurosonogram factors related with neonatal seizures in Visakhapatanam, India. Methods: The study was carried out in the Department of Paediatrics, Andhra medical college, King George Hospital, Visakhapatnam, Andhra Pradesh. The study was done to assess the biochemical changes, nurosonogram factors and microbilogical organisms implicated in neonatal seizures. Results: The present study is descriptive in nature where clinical spectrum of neonatal seizures in neonates was studied. 1500 neonates were admitted in NICU during the study period, among them 200 (13.3%) developed neonatal seizures. Etiology in majority of the cases of neonatal seizures was hypoxic ischemic encephalopathy (45%) followed in frequency by intracranial haemorrhage (14%), meningitis (12%), hypoglycaemia (11%), hypocalcaemia (4%) and others (14%). The most common organism implicated in neonatal seizures was Escherichia coli (36%), followed by Klebsiella (30%), staphylococcus aureus (19%), Streptococci agalactiae (7%) and unknown (8%). Meningitis accounted for 12% of neonatal seizures. Most common biochemical abnormalities noted were hypoglycemia, hypocalcaemia and hyponatremia. Conclusions: Biochemical abnormalities may significantly contribute to seizure activity and possibly correction of these abnormalities may play a significant role in seizure control. A biochemical work up is necessary for all cases of neonatal seizures. Appropriate treatment with antibiotics is essential. Examination of cerebrospinal fluid is essential work up in cases of neonatal seizures. Neurosonogram had good potential in predicting neurological outcome in neonates with perinatal asphyxia. Neurosonogram should be incorporated in the routine evaluation of seizures.